Case report: How I do it? Laparoscopic hepatectomy with transcatheter arterial ICG staining for hepatolithiasis review - Xu, Jingyi; Qian, Xinye; Yang, Wei; Yu, Fei; Yang, Yufan; Hu, Wang; Gao, Lu; Wang, Shuang; Wu, Liusheng; Zhao, Yutong; Yang, Lei; Zhang, Lin; et al. (Frontiers in Medicine, 2024)
Background: Hepatolithiasis is regarded as the presence of stones in the intrahepatic bile ducts. Recurrent inflammation of bile ducts can bring many bad effects. How to completely remove stones is still a challenge.Presentation: A 66 years old male went to our hospital because of h hepatolithiasis and choledocholithiasis. Selective hepatic arteriography and transcatheter arterial embolization followed by laparoscopic watershed hepatectomy under fluorescent navigation and laparoscopic common bile duct exploration on mass removal is performed.Clinical discussion: For patients who suffer from hepatolithiasis, the main treatment principles of the operation are to remove the stones, correct the stenosis and prevent recurrence. The laparoscopic watershed hepatectomy under fluorescent navigation can provide important support for precision liver surgery, which can give some suggestions for future hepatectomy.Conclusions: Based on 3D visual watershed analysis, trans-arterial DSA positive fluorescence navigation has some advantages, which successfully overcomes the shortcomings of reverse staining method and positive staining method.